Differences in some kinematic parameters in pole vaulters of different qualities - Moguš, D.; Jukic, J.; Cavala, M. (Sport Science - International Scientific Journal of Kinesiology, 2018)
The aim of this study was to determine the differences in certain kinematic parameters of pole vaulters with different qualities and sports performance. For this purpose, the jumping performances of the pole vaulters with different qualities were analyzed to determine jumping performance and success. From the observed kinematic parameters analyzed in this study, it can be concluded that the subjects differ mostly in the variable velocity that is achieved at the end part of the run up prior to take off, the angle of ascent of the body, the duration of the take off and the difference of the height of the pole vaulters grip on the pole and the height that is cleared. Achieving a greater horizontal speed and maintaining that speed into the take off, a powerful take off and an optimal take off position of the body with a fast bending of the pole will accumulate a large amount of kinetic energy into the pole that will ultimately provide a better performance and result. Result efficiency in the pole vault is primarily determined by variables defined by motor abilities as well as by indicators for which jumping technique has been determined. The results of the research can be used by sports coaches in the programming of the training process.